Association Between BRCA1 Expression Status and Breast Cancer Metastasis Index (cM) in West Nusa Tenggara - Alia, Alia; Lestari, Rizka Vidya; Kusuma, Yan Adhitya (Jurnal Biologi Tropis, 2026)
Breast cancer remains a major cause of mortality among Indonesian women, with metastasis as its primary prognostic determinant. Although BRCA1 is a key tumor suppressor involved in genomic stability, its association with the breast cancer metastasis index in Indonesian patients remains limited. This research was designed to evaluate the association between BRCA1 expression and breast cancer metastasis index (cM), as well as differences in BRCA1 expression across metastasis categories. A cross-sectional observational study design was employed using 32 samples selected by purposive sampling, consisting of medical records and paraffin-embedded tissue blocks obtained from Pathology Anatomy Laboratory of the NTB provincial hospital. BRCA1 expression was assessed by immunohistochemistry. Bivariate analysis between variables was performed using the Fisher’s Exact test. Of 32 patients, 78.1% were classified as cM1. No significant association was identified between BRCA1 expression and metastasis index (p = 0.394), although low BRCA1 expression was descriptively more frequent in metastatic cases. BRCA1 expression alone is not an independent determinant of metastasis in breast cancer patients in NTB. This suggests that metastasis is multifactorial. Studies with larger samples and additional biomarkers such as hormonal receptors, proliferation index, and metastasis-related proteins are suggested to investigate the metastatic risk in this population.